Emerging Role of Robot-Assisted Occupational Therapy for Children with Down syndrome - Krasniqi, Venera; Ackovska, Nevena; Zdravkova, Katerina (My University, 2017)
Robotic technology is becoming increasingly popular as a platform for both education and entertainment. It also provides us with new conceptual directions which might have incredibly positive impact on children with physical growth delays and intellectual disabilities. In this research project, the educational robot Roamer Too from Valiant Technologies has been used to explore the development of social skills of children with Down syndrome. In conjunction with an interactive collaborative environment, this device represents a unique opportunity for these children to fully engage in learning, play, communication, build relationships and have fun. The results of this study indicate that educational robots help to develop kids’ social and learning psychologies, moving from a more standard knowledge acquisition by absorption toward acts of exploration, collaboration, and creation. As a result, children reflect social initiations, communicative competence and joint attention.
Keywords: Robot, children, Down syndrome, education, social